Framing Effect, Loss Aversion, and Self-Control in Gen Z Investment - Gusni Gusni; Rahma Nurbahira (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
Investment decisions are a complex process influenced by various psychological and behavioral factors, particularly among younger generations. In the capital market, these decisions are shaped by investor behavior in allocating funds to achieve future returns. Since investment is a long-term commitment, thorough analysis is essential, especially in managing potential risks. This study explores the influence of the framing effect, loss aversion, and self-control on the investment decisions of Generation Z. The research subjects consisted of Widyatama University students who are active investors, selected using the Tabachnick & Fidell method. This study employs multiple linear regression analysis to examine the relationships between variables. The findings indicate that the framing effect, loss aversion, and self-control positively impact the investment decisions of Generation Z students at Widyatama University. These results offer valuable insights for capital market policymakers to mitigate behavioral biases among young investors, helping to minimize negative effects on market volatility.